THE TREND OF ANNULMENT OF MARRIAGE ON THE TERRITORY OF UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2023)
This article shows the statistics of rulings in Uzbekistan and their impact on the socio-economic life of minors. A collection of information obtained throughout Uzbekistan, showing the procedure and system of annulment of marriage. 20-year dynamics of children in orphanages, that is, indicators of children who have lost their parents or are psychologically and physiologically unhealthy.